Utilization of ion exchange together with membrane processes for wastewater reclamation and reuse - Kabay, Nalan; Arda, Muserref; Bunani, Semyuel; Altıok, Esra; İpekçi, Deniz; Hacıfazlıoğlu, Mertkan; Parlar, Ilker; Yılmaz İpek, Idil; Yüksel, Mithat (My University, 2016)
Ion exchange resins and membranes could be successfully used in integrated systems for elimination of some pollutants, recovery of valuable substances from water and for polishing RO permeate of desalination plants. Ion exchange membranes in an electrodialysis (ED) system could be employed for the post-treatment of concentrate streams of NF/RO processes and for valorization of RO desalination brines. The ED process in combination with bipolar membranes (BMED) was developed to split an aqueous saline solution into its corresponding acid and base without addition of any chemicals. Electrodeionization (EDI) system could be also another alternative method for boiler feed water production from RO permeate of raw water. This presentation will focus on elaboration of new ideas for the utilization of ion exchange in the process schemes of wastewater treatment based on membrane technologies.
Keywords: ion exchange; desalination; membrane process; wastewater treatment; іонний обмін; опріснення води; мембранний процес; очищення стічних вод; ионный обмен; опреснение воды; мембранный процесс; очистка сточных вод